2021
DOI: 10.3390/toxins13080509
|View full text |Cite
|
Sign up to set email alerts
|

Differing Effects of Vinegar on Pelagia noctiluca (Cnidaria: Scyphozoa) and Carybdea marsupialis (Cnidaria: Cubozoa) Stings—Implications for First Aid Protocols

Abstract: The jellyfish species that inhabit the Mediterranean coastal waters are not lethal, but their stings can cause severe pain and systemic effects that pose a health risk to humans. Despite the frequent occurrence of jellyfish stings, currently no consensus exists among the scientific community regarding the most appropriate first-aid protocol. Over the years, several different rinse solutions have been proposed. Vinegar, or acetic acid, is one of the most established of these solutions, with efficacy data publis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Herein, we have demonstrated that vinegar application is strictly contraindicated for A. viridis stings due to its potential as an activating solution (Table 1), producing a worsening of the affected area. This is also the case in other species of scyphozoans and hydrozoans [29,33,36,53], including the most important Mediterranean jellyfish P. noctiluca [29], which is responsible for the majority of jellyfish sting cases seeking assistance from lifeguards in certain Mediterranean beaches [18].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Herein, we have demonstrated that vinegar application is strictly contraindicated for A. viridis stings due to its potential as an activating solution (Table 1), producing a worsening of the affected area. This is also the case in other species of scyphozoans and hydrozoans [29,33,36,53], including the most important Mediterranean jellyfish P. noctiluca [29], which is responsible for the majority of jellyfish sting cases seeking assistance from lifeguards in certain Mediterranean beaches [18].…”
Section: Discussionmentioning
confidence: 96%
“…Updated first-aid protocols based on scientific advances are essential tools to prevent harm. In recent decades there has been a growth in scientific reports warning of the ineffectiveness of vinegar as a rinse solution for the treatment of cnidarian stings [29,33,35,36,53], with the exception of cubozoans where its use is effective [29,33,34]. Immediate A. viridis cnidocyst discharge was observed after vinegar application (Figure 4C), indicating it should not be used as a rinse solution following a snakelocks sea anemone sting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations